Chairman - Chrysostomou, Christis (My University, 2026)
Coordination of the planning of the adoption and the implementation of Structural Eurocodes in the Republic of Cyprus. The work consisted, among other things, of the preparation of the National Annexes of the Eurocodes and the training of engineers (through a life-long education program) in the correct application of the Eurocodes. The budget for this program is 680 000 Euro for three years